Influence of Coronal Holes on CME Deflections: Numerical study - Sahade, Abril (2020)
The understanding of the causes that produce the deflection of coronal mass ejections (CMEs) is essential for the space weather forecast. We study the effects on CME trajectories produced by the different properties of a coronal hole (CH), close to the ejection area. We perform ideal magnetohydrodynamics simulations emulating the early rising of the CME in the presence of a CH. We find that, the stronger the magnetic field and the wider the CH area, the larger the CME deflection. The deflection reduces as the CH moves away from the ejection region. To quantify the deflection we propose a dimensionless parameter that depends on the CH properties. We show that a minimum magnetic energy region, responsible for the deflection, is associated with the presence of the CH near the CME. We establish a relationship between the CH properties, the location of the minimum magnetic region, and the CME deflection.